Radar-absorbing nickel-coated fabric composite for wing-shaped structure in the X-band. (1st May 2020) - Choi, Won-Ho; Kwak, Byeong-Su; Noh, Yeong-Hoon; Yook, Jong-Gwan; Kweon, Jin-Hwe; Nam, Young-Woo
Abstract: This study presents a thin radar-absorbing nickel-coated fabric composite through an electroless plating technique for wing-shaped structure to reduce the radar cross section (RCS) in terms of a practical application. The newly proposed absorber with high permittivity of NCF can accomplish high absorption performance on a curved surface at the target frequency. The NCF was fabricated using an electroless plating process, which is suitable for mass production. Utilizing the concept of the change in surface resistance depending on skin depth, the NCF absorption mechanism was discussed. From the interlaminar shear strength (ILSS) test, it was confirmed that the interfacial adhesion properties between the fiber and polymer matrix caused no serious degradation to the mechanical properties and structural integrity. The total thickness of the designed NCF RAS with optimization process for the X-band target is 2.02 mm, which is a very thin thickness compared with previous reported RAS. To demonstrate absorption and RCS reduction on a curved surface, a planar and wingbox with leading edge of NCF RAS were fabricated and measured. Although the planar NCF RAS showed a slightly smaller absorption bandwidth than previous RASs, the proposed absorber demonstrated excellent performance in RCS reduction despite its thin thickness.